EVALUATION MODEL IN DEVELOPING SOYBEAN AREA ACTIVITIES IN WEST LAMPUNG REGENCY - Sartono Sartono; Risal Risal; Endang Kristiawati (Program Studi Magister Manajemen, 2023)
The objectives of this study are to (1) Identify the background and objectives of soybean area development activities in West Lampung Regency, (2) Identify supporting resources for the implementation of soybean area development activities in West Lampung Regency, (3) Identify the suitability of the goals and objectives of soybean area development activities in West Lampung Regency with their implementation (4) Identify the benefits/impacts of the implementation of soybean area development activities in West Lampung Regency on the local government (West Lampung Regency) and for farmers. This research is based on the CIPP evaluation model with a qualitative approach. The sampling was 43 people. The data obtained came from primary and secondary data. Data collection used observation techniques, interviews, literature studies, and questionnaires. The results of the research from the evaluation results (1) Context evaluation that the background and objectives of the activity are in accordance with law number: 22 of 2019 and Regulation of the Minister of Agriculture number: 18/PERMENTAN / RC.040 /4/2018, (2) Input evaluation states that all supporting aspects such as human resources, socialization, production facilities, and budgets already have a basis/guidelines for implementation, only need improvement, namely the production facilities provided must be in accordance with soybean cultivation standards, (3) Process evaluation all aspects are appropriate, only need improvement, namely optimizing the role of farmers, (4) Product evaluation that the results of the implementation of activities have had a lot of impact on farmers as implementers of activities although not yet optimal, Farmers get additional income while the benefits for local governments are the addition of soybean planting areas in West Lampung Regency but production is not optimal, namely production of 123 tons/hectare of the target of 425 tons/hectare or realized 29%.